The Influence of Job Characteristics on Job Application Intention Through Employer Attractiveness as a Mediating Variable on Generation Z in the Indonesian Pharmaceutical Manufacturing Industry - Kusumawan, Ardhian Tirta; Sary, Fetty Poerwita (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The pharmaceutical manufacturing industry in Indonesia faces increasing challenges in attracting Generation Z talent. Understanding the factors influencing their intention to apply for a job is crucial for maintaining competitiveness and innovation. Generation Z has a lower intention to apply for jobs in the manufacturing sector compared to the informal and service sectors. This is due to their preference for flexibility and autonomy, which are often limited in manufacturing. The strict regulations to ensure product quality and safety, rural factory locations, and shift-based work systems make manufacturing less appealing to them. This study aims to identify the factors influencing the intention to apply for a job among Generation Z in Indonesia’s pharmaceutical manufacturing sector. A quantitative approach was used, involving 204 Generation Z employees across Indonesia. Most respondents are contract-based with less than two years of experience, offering insights into early-career perspectives. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that job characteristics significantly influence the intention to apply for a job, both directly and indirectly through employer attractiveness. Employer attractiveness also has a significant direct effect on the intention to apply for a job. These findings suggest that improving job design and strengthening employer branding are effective strategies to attract Generation Z. The study offers practical implications for HR practices in the pharmaceutical manufacturing industry.